Landscape connectivity explains interaction network patterns at multiple scales - Santos, Micaela (2019)
Under a metacommunity framework, the spatial configuration of habitat fragments could determine local community structure. Yet, quantifying fragment connectivity is challenging, as it depends on multiple variables at several geographical scales. We assessed the extent to which fragment connectivity and area explain patterns in interaction structure among four herbivore guilds and their host plants in a metacommunity. We propose an integrative connectivity metric including geographic distance, neighboring fragment area and similarity in resource composition as an extension of Hanski’s classic metric. We then used nonlinear models to assess whether fragment connectivity and area predicted link richness and similarity in link composition. We found that link richness was always negatively related to connectivity but at different geographic scales depending on the herbivore guild. In contrast, while link composition was also related to connectivity, the direction and strength of this relationship varied among herbivore guilds and type of link composition (qualitative or quantitative). Furthermore, focal fragment area was not an important determinant of interaction diversity in local communities. Our findings emphasize resource similarity as a novel dimension of fragment connectivity relevant in explaining interaction diversity patterns in natural trophic networks.